Competency-based curriculum, relevant second language learning theories, and its language assessment - Hendra Heriansyah; Pharisaa Darni; Rahmat Fajri; Rosnani Sahardin (Universitas Syiah Kuala, 2021)
The complexity of problems encountered in today’s world has forced educational institutions to re-envision their mission in order to successfully prepare a competent and skilled alumna who is able to face the future challenges on a global scale. To achieve this goal, a strategic policy and management, which involves different stakeholders and other parties, are needed. To prepare a competent human resource that is able to face each of the challenges and changes, a curriculum is required that meets the established standards as well as the job market demands. In this regard, this paper addresses the implementation of competency-based curriculum (CBC) in Indonesia. The introduction explains the overview of CBC, its aim and implementation, the relationship between English curriculum and environment, and English language syllabus. The second part discusses the main principles of the curriculum, the theoretical approach that relates to language description and some theories of second language learning that underpin the curriculum. Additionally, other factors that relates to curriculum such as the context and the assessment system including language curriculum innovation are also explored. The third part is the conclusion and identification which reports some of the unsolved issues that relates to the implementation of the curriculum.